Pergeseran Nilai Tradisi Wiwitan di Desa Mangunan Kecamatan Dlingo Kabupaten Bantul Yogyakarta Tahun 2010-2019 - ristiantie, yenny (Universitas PGRI Yogyakarta, 2020)
This study aims to provide information about the history, processions and shifting values that occur in the Wiwitan Tradition in Mangunan, Dlingo, Bnatul, Yogyakarta and the factors behind it. This study used qualitative research methods. Data collection techniques with observation, interviews and documentation. The data analysis technique used was data collection, data reduction, data presentation and conclusion drawing. The results of this research is that the history Wiwitan Tradition which going on for hundreds of years. The stages in the Wiwitan Tradition are the stages of preparation and implementation. The form of a shift in the value of the Wiwitan Tradition is in the form of shift in value in terms of economy, social, tourism, religion and spirituality. The shift in value that occurs is caused by external factors and internal factors.